Community Responses to Nature-based Tourism Promotion Materials in Indonesia - Rini Untari; Ricky Avenzora; Dudung Darusman; Tutut Sunarminto (Jurnal Manajemen Hutan Tropika, 2019)
The growth of nature-based tourism has triggered further development of outdoor tourism activities by utilizing natural areas for commercial purposes. This trend is likely related to the role of tourism promotion. However, promotion is still interpreted partially as an effort to convey information persuasively to reach the phase of purchasing. In this study we used more comprehensive and integrated approach. We interpret promotion in seven phases from information sharing up until becoming a tourism promotion agent so that promotion of nature-based tourism destinations is more effective and optimal. This study is aimed at determining the role of promotion on visitor decisions to visit nature-based tourism destinations. A set of questionnaire was distributed to the community by considering the different income level, education, and occupation divided into three categories, namely, the upper, middle, and lower classes. In this study we used 100 respondents to assess printed promotional and audio-visual materials. Data were analyzed using One Score One Indicator System, Kruskal Wallis, and Dunn test. The results of the study showed that out of the seven phases that we examined, differences of opinion occurred in three phases of promotion including recognition and consideration phase, the motivation to enjoy natural tourism services, and willingness to be tourism promotion agent. This indicates differences of opinion over the factors that influence the three categories of respondents regarding the decision to visit a promoted nature-based tourism destination. Higher income shows a better response to the seven phases of the promotion definition of natural tourist destinations. We identified that internal factors including income characteristics, education, and occupation in addition to external factors of promotional materials (such as design and substance) together with attraction (destination attributes) can increase the the decision to visit nature-based tourism destinations. The management implications of this study were relate to consumer behavior on visit decisions as the important factor for the success of the destinations. Also, designing effective promotional activities that are tailored to the perceptions and motivations of consumers in nature-based tourism destinations is important.